Desenvolvimento de um microerosómetro do tipo TMEM para aplicação em plataformas rochosas litorais - Neves, Mário; Pereira, Ana Ramos; Laranjeira, Manuela; Trindade, Jorge (Finisterra, 2001)
DEVELOPMENT AND APPLICATION OF A TRAVERSING MICRO-EROSION METER FOR SHORE PLATFORMS – The study of the shore platforms specific environmental conditions requires accurate equipment to measure erosion rates. In this paper, the construction details of a Traversing Micro-Erosion Meter (TMEM) is described. This TMEM adds some improvements to previous devices that aim to increase the data set collected, both in quality and in quantity. The installation and measurement procedures are described, as well as the advantages and limitations of this equipment. An experimental survey was carried out within the tidal range of the limestone shore platform of Tombadoiros, in a sector of the Portuguese western coast. For a 96 days period in the autumn/winter of 2000/2001, the mean rate of erosion at the site was 0,153mm/year. However, this result includes disturbances associated with the settlement of the black lichen Verrucaria maura in 58 % of the measuring points. It was found that the mean rate of erosion in the clean rock surface was 2,5 higher when compared to the area colonized by the lichen.